Finance, firm size, and growth - Beck, Thorsten, 1967- 1967-; World Bank (Policy research working paper, 2005)
"The authors examine whether financial development boosts the growth of small firms more than large firms and hence provides information on the mechanisms through which financial development fosters aggregate economic growth. They define an industry's technological firm size as the firm size implied by industrial specific production technologies, including capital intensities and scale economies. Using cross-industry, cross-country data, the results indicate that financial development exerts a disproportionately large effect on the growth of industries that are technologically more dependent on small firms. This suggests that financial development accelerates economic growth by removing growth constraints on small firms and also implies that financial development has sectoral as well as aggregate growth ramifications. This paper--a product of the Finance Group, Development Research Group--is part of a larger effort in the group to understand the growth finance link"--World Bank web site